Optimizing Manahij al-Tarjamah Learning Outcomes: A Goal-Free Evaluation of Contextual Systemic Collaboration - Ade Agung Prayoga; Musleh Harry; Welly Kuswanto (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
This study examines the consequences of contextual systemic collaboration in a Manahij al-Tarjamah course without using the programme's declared objectives as the initial frame of judgment. A qualitative goal-free evaluation was conducted to identify actual, unintended, positive, and constraining effects emerging from Arabic-Indonesian translation learning. The evidence corpus comprised lecturer and student interviews, classroom observations, reflective records, peer-feedback traces, and translation artefacts associated with contextual cases. ATLAS.ti was used to organise document groups, conduct open and process coding, compare code-document patterns, develop analytic memos, and construct a network of consequences. To reduce goal contamination, formal course targets were withheld during first-cycle coding and consulted only after the emergent effect map had stabilised. The analysis produced six interrelated findings. Contextual cases shifted students from method naming toward situational diagnosis; role-based collaboration made translation reasoning more visible; multi-source feedback deepened revision; digital tools broadened alternatives but also created verification dependency; reflective portfolios strengthened evaluative judgment and professional identity; and linguistic accuracy, participation equity, and fidelity-readability trade-offs remained uneven. An unintended benefit was the emergence of a shared metalanguage for defending translation decisions. Unintended burdens included documentation fatigue, time pressure, and the possibility that assigned roles became procedural rather than genuinely collaborative. The goal-free judgment is therefore conditional: contextual systemic collaboration optimised reasoning, feedback uptake, and revision more consistently than it optimised all features of final-text accuracy. The study recommends a genre-balanced case bank, rotating role audits, staged feedback, machine-translation literacy protocols, terminology calibration, and concise decision memos. It contributes a consequence-centred evaluation framework for translation-methodology courses in Arabic higher education.